Effects of an Enzymatically Depolymerized Heparin as Compared with Conventional Heparin in Healthy Volunteers - Mätzsch, Thomas; Bergqvist, David; Hedner, Ulla; Østergaard, Per (Thrombosis and Haemostasis, 1987)
A low molecular weight heparin (LMW-heparin) with a mean molecular weight of 4900 dalton was prepared by controlled enzymatic depolymerization of conventional porcine mucosal heparin. The effects of 2,500, 5,000 and 10,000 U (Xal; 29,58 and 116 mg) on factor Xa inhibition (Xal), factor Ila inhibition (Hal), APTT, AT III and platelet count were compared to those of 5,000 U (Xal; 26 mg) of conventional heparin given s. c. to 6 healthy volunteers. 5,000 U (Xal; 58 mg) of LMW-heparin was given i. v. A dose related response with regard to the Xal and the Ila-inhibitory activities with peak values at 4 hours after the s. c. injections was obtained. An increase of the Xal/IIal ratio over the time after injection was seen only after i. v. administration of the LMW-heparin. The APTT was only slightly prolonged and remained within normal range after s. c. injection. AT III and platelet counts were unaffected. The biological half life of the LMW-heparin was 111 minutes if assayed by Xa inhibition, 76 minutes if assayed by Ila inhibition and 40 minutes if assayed by APTT. A strong correlation between the Xal activities obtained and body weight was seen, indicating that LMW-heparin should be administered individually according to body weight.
Keywords: Heparin; Low molecular weight heparin; Pharmakokinetics; Enzymatic depolymerization